Biomaterial and biomechanical considerations to prevent risks in implant therapy. Issue 1 (12th August 2019) - Bonfante, Estevam A.; Jimbo, Ryo; Witek, Lukasz; Tovar, Nick; Neiva, Rodrigo; Torroni, Andrea; Coelho, Paulo G.
Abstract: This paper is aimed to present a biomaterials perspective in implant therapy that fosters improved bone response and long‐term biomechanical competence from surgical instrumentation to final prosthetic rehabilitation. Strategies to develop implant surface texturing will be presented and their role as an ad hoc treatment discussed in light of the interplay between surgical instrumentation and implant macrogeometric configuration. Evidence from human retrieved implants in service for several years and from in vivo studies will be used to show how the interplay between surgical instrumentation and implant macrogeometry design affect osseointegration healing pathways, and bone morphologic and long‐term mechanical properties. Also, the planning of implant‐supported prosthetic rehabilitations targeted at long‐term performance will be appraised from a standpoint where personal preferences (eg, cementing or screwing a prosthesis) can very often fail to deliver the best patient care. Lastly, the acknowledgement that every rehabilitation will have its strength degraded over time once in function will be highlighted, since the potential occurrence of even minor failures is rarely presented to patients prior to treatment.